Vocabulary in high-school EFL textbooks: Texts and learner knowledge. (October 2020) - Sun, Ye; Dang, Thi Ngoc Yen
Abstract: High school education is an important stage of foreign language education. This study examined the vocabulary in a 273, 094-word corpus of high school EFL textbooks in China and measured the vocabulary knowledge of 265 high school students who used these textbooks. The corpus analysis showed that 3000 word-families and 9000 word-families were needed to reach 95% and 98% of the whole textbook corpus, respectively. However, vocabulary size needed for comprehension of each textbook varied greatly and did not always correspond to the textbook levels. Additionally, while the most frequent 1000 words were fairly well-represented in the textbooks, the 2nd and 3rd most frequent 1000 word-families were not. Scores on Webb, Sasao, and Ballance's (2017) Updated Vocabulary Levels Test revealed that the majority of the students either had mastered only the most frequent 1000 words or had not mastered any 1000-word levels. Pedagogical implications for high school EFL textbook writers, program managers, and teachers are discussed.